KANNADA VACHANA BHARATA - Dalavai, Kasturevva Basappa (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In the ancient literature of our country, a tradition of recreating the Mahabharata, which is famous as an epic or history, in the vernacular languages ​​has grown very richly. Adikavi Pampa’s Vikramarjuna Vijayam, Kumaravyasana’s Karnata Bharata Kathamanjari, Paramadeva Kaviya Turanga Bharata, Sukumarabharatiya’s Chayana Bharata, Suta Bharata and so on have been composed in the form of poetry in the context of Old Kannada and Middle Kannada. Each poem is unique in its own way. In the context of New Kannada prose, the one that contains such features and has gained the greatest popularity and popularity and is considered a masterpiece is; Vachana Bharata by A. R. Krishnashastri. Those who want to write in Kannada should read Shastri’s Vachana Bharata not just once or twice, but dozens of times to refine their writing style and move forward, recommends D. V. G.